EULAR response criteria for polymyalgia rheumatica: results of an initiative of the European Collaborating Polymyalgia Rheumatica Group (subcommittee of ESCISIT). Issue 12 (21st November 2003) - Leeb, B F; Bird, H A; Nesher, G; Andel, I; Hueber, W; Logar, D; Montecucco, C M; Rovensky, J; Sautner, J; Sonnenblick, M
Abstract : Objective: To develop response criteria for polymyalgia rheumatica (PMR) for monitoring treatment and comparing alternative treatments regimens. Methods: 76 patients, mean (SD) age 68.7 (7.7) years, were enrolled. Corticosteroids, and non-steroidal anti-inflammatory drugs (NSAIDs) were the only drugs allowed during the observation period. Erythrocyte sedimentation rate (ESR), C reactive protein (CRP), α2 globulin, serum iron, pain, physician's global assessment (PGA), morning stiffness (MST), muscle tenderness (MT), myalgia, and the elevation of upper limbs (EUL) were determined regularly. The daily corticosteroid and NSAID doses as the corticosteroid response time were recorded. To ensure evaluation of an adequate number of patients (n = 57) week 24 was chosen for final analysis. Results: ESR, CRP, α2 globulin, pain, PGA, MST, myalgia, MT, and EUL showed significant improvement (p<0.0001) at week 24 compared with week 0. Multiple regression analysis showed that changes of ESR (p = 0.08), CRP (p = 0.41), α2 globulin (p = 0.13), MST (p = 0.1), and MT (p = 0.07) were independent of pain, but myalgia (p<0.001) and EUL (p = 0.003) were pain dependent. Consequently, a core set of PMR response criteria, comprising ESR or CRP, pain, PGA, MST, and EUL was established. Assessment of treatment responses with this core set resulted in 90%, 70%, 50%, and 20% improvement in 31/57 (54%), 46/57 (81%), 51/57 (89%), and 54/57 (95%) of the patients, respectively. Conclusion: These PMR response criteria are a promising tool for better monitoring of disease activity and treatment in PMR. It is proposed that these criteria should be used in clinical trials in the near future to explore alternative treatment options for PMR.